A novel miniature coplanar band-pass filter for ISM applications - Badr Nasiri; Abdelhadi Ennajih; Ahmed Errkik; Jamal Zbitou; Mounir Derri (Institute of Advanced Engineering and Science, 2020)
This paper presents a novel approach to design a compact miniature coplanar band-pass filter by using rectangular split ring resonator. This proposed circuit is designed for the Industrial, Scientific and, Medical (ISM) frequency band applications at 2.4 GHz. At the first stage, a metamaterial resonator is designed and simulated in a TEM waveguide to verifiy its electromagnetic proprieties around the desired frequency bands. At the second stage, a band pass filter is designed using the proposed metamaterial resonator. Many parametric studies are realized to investigate the effect and influence of some resonator parameters on the proposed BPF performances. ADS Agilent and CST-MWS solvers are used in order to verify the simulated results. The circuit frequency responses show an excellent insertion loss and good return loss in the passband.